Socio-Demographic Factors Impact Disabilities Caused by Perinatal Asphyxia among Chinese Children - Ao, Deng; Guo, Shuai; Yun, Chunfeng; Zheng, Xiaoying (PLoS ONE, 2021)
Background Disabilities caused by perinatal asphyxia will burden child health and well-being. To date, our understanding about the situation and risk factors of perinatal asphyxia-induced disabilities among Chinese children is still limited. Objectives To evaluate the prevalence and socio-demographic risk factors of disabilities caused by perinatal asphyxia among Chinese children in 2006 and compare disability trajectories across different socio-demographic status. Methods Cross-sectional data came from the 2006 China National Survey on Disability which includes a total of 616,940 children aged 0– 17 years old was employed in the investigation. Perinatal asphyxia-induced disabilities were identified by following the guidance in consensus manuals. Population-weighted numbers and prevalence rates were investigated, and multivariable logistic regression was performed to evaluate associations between disabilities and socio-demographic factors. Adjusted predictions at representative values were computed to compare the disability trajectories relative to significant socio-demographic variables. Results The prevalence rate of disabilities caused by perinatal asphyxia was 7.70 per 10,000 children (95% CI: 7.01– 8.39). Male (OR 1.81, 95% CI: 1.47– 2.23) and low family income (OR: 1.73, 95% CI: 1.21– 2.49) have higher and the increase of per additional year of age (OR: 0.89, 95% CI: 0.88– 0.91) has lower probability of being disabilities caused by perinatal asphyxia. Further disability trajectories showed that differences in probability between gender and family income group were more evident before age 7 and weakened with increasing age. Conclusions Our results showed that both demographic and socioeconomic characteristics are risk factors for disabilities caused by perinatal asphyxia. Of these, gender and family income have much higher impact than other factors on the prevalence rate of disabilities caused by perinatal asphyxia at infants and young children. Multiple society sectors should increase their effort to bring about fundamental social change to prevent disabilities caused by perinatal asphyxia, especially concerning younger children and their families.